2010
DOI: 10.1126/science.1190482
|View full text |Cite
|
Sign up to set email alerts
|

In-Plane Resistivity Anisotropy in an Underdoped Iron Arsenide Superconductor

Abstract: High-temperature superconductivity often emerges in the proximity of a symmetry-breaking ground state. For superconducting iron arsenides, in addition to the antiferromagnetic ground state, a small structural distortion breaks the crystal's C(4 )rotational symmetry in the underdoped part of the phase diagram. We reveal that the representative iron arsenide Ba(Fe(1)(-x)Co(x))(2)As(2) develops a large electronic anisotropy at this transition via measurements of the in-plane resistivity of detwinned single crysta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

93
998
7
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 843 publications
(1,106 citation statements)
references
References 27 publications
93
998
7
3
Order By: Relevance
“…2(b) shows that, in fact, T f l displays a non-monotonic dependence on Co doping, with a minimum for x ≈ 0.02 to 0.03. Interestingly, Jiun-Haw Chu et al 9 have recently reported a maximum electronic nematic order over the same range of Co concentrations, around the onset of bulk superconductivity (x = 0.03). This suggests a maximum orbital order around the onset of bulk SC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2(b) shows that, in fact, T f l displays a non-monotonic dependence on Co doping, with a minimum for x ≈ 0.02 to 0.03. Interestingly, Jiun-Haw Chu et al 9 have recently reported a maximum electronic nematic order over the same range of Co concentrations, around the onset of bulk superconductivity (x = 0.03). This suggests a maximum orbital order around the onset of bulk SC.…”
Section: Resultsmentioning
confidence: 99%
“…2,8 However, the large electronic anisotropy revealed in Ba(Fe 1−x Co x ) 2 As 2 precisely where the crystal's C 4 rotational symmetry is broken can not be explained based on the 1% lattice distortion at T s . 9 In fact, it has been shown the presence of a C 4 structural to C 2 electronic symmetry transition in the quasi-particle interference maps of Ca(Fe 1−x Co x ) 2 As 2 . 10 This electronic symmetry transition could be a result of orbital ordering due to the above mentioned inequivalent occupation of the d xz and d yz orbitals.…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8] In the cuprates, nematic order is signaled by the anisotropy of resistivity and bond ordered density [2][3][4][5][6] . In the pnictides, orthorhombic structure distortion is ubiquitous, and is confirmed by various tools such as neutron scattering 9 , STM 10 , transport [11][12][13] , and ARPES 14 . A natural question associated with nematic ordering is its interaction with other order parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Studies of the in-plane resistivity 6 showed that the effect is the largest at low doping x∼2-4% in Ba(Fe 1−x Co x ) 2 As 2 , but it is present even in the undoped limit x=0 at low temperatures, i.e. in the magnetically ordered state with wavevector (π,0).…”
mentioning
confidence: 99%